Prehospital triple antiplatelet therapy in patients with acute ST elevation myocardial infarction leads to better platelet aggregation inhibition and clinical outcome than dual antiplatelet therapy. Issue 22 (3rd October 2010) - Smit, Jaap Jan J; van Werkum, Jochem W; ten Berg, Jurrien; Slingerland, Robbert; Ottervanger, Jan Paul; Heestermans, Ton; Dill, Thorsten; Hamm, Christian; van 't Hof, Arnoud W J
Abstract : Objective: To assess whether prehospital initiation of high-dose tirofiban in addition to high-dose clopidogrel results in more adequate inhibition of platelet aggregation (IPA) and better clinical outcome after primary percutaneous coronary intervention (PCI). Methods: Prespecified two-centre substudy of the prospective, international, multicentre, placebo controlled Ongoing Tirofiban in Myocardial Infarction Evaluation trial 2 (On-TIME-2 trial). 648 of 964 (67%) patients in the On-TIME-2 trial with ST elevation myocardial infarction undergoing primary PCI were studied. Pre-PCI IPA after early prehospital initiation of high-bolus dose (25 μg/kg) tirofiban was compared to placebo in addition to acetylsalicylic acid, unfractionated heparin and 600 mg clopidogrel. Results: IPA was measured at a median of 60 min after study medication administration. In all four tests: Fe induced platelet aggregation, ADP induced platelet aggregation, platelet function analyser (PFA)-100 (collagen–epinephrine and collagen–ADP cartridge) IPA was higher in patients pretreated with high-dose tirofiban (p<0.001 for all tests), even after >74 min of pretreatment. Patients in the highest quartile of IPA had less residual ST segment deviation 1 h post-PCI (p value for trend: p=0.001, 0.004, 0.001, 0.002 respectively). There was a significant relationship between PFA-100 (both cartridges) and major adverse cardiovascular events (MACE, p=0.028, p=0.035) and early thrombosis (p=0.009, p=0.007). Conclusions: 60 min of prehospital initiated antiplatelet treatment including high-dose tirofiban resulted in higher levels of IPA compared to pretreatment with acetylsalicylic acid and high-dose clopidogrel alone, even after longer pretreatment times. Levels of IPA were significantly related to ST resolution and MACE, including stent thrombosis. This substudy confirms the main findings of the On-TIME2 trial that clopidogrel alone is suboptimal, even at high dose and administered well in advance of primary PCI.